2019
DOI: 10.1039/c9qm00154a
|View full text |Cite
|
Sign up to set email alerts
|

A novel family of AIE-active meso-2-ketopyrrolyl BODIPYs: bright solid-state red fluorescence, morphological properties and application as viscosimeters in live cells

Abstract: AIE-active and bright solid-state red-emissive meso-2-ketopyrrolyl BODIPYs have been developed as viscosimeters in live cells for real-time quantification of intracellular viscosities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 79 publications
1
32
0
Order By: Relevance
“…This is resulting from the efficiently restricted ESDBR effect by the intermolecular H‐bonding interaction upon fluoro‐substitution. Furthermore, according to Förster–Hoffmann power‐law relationship, the relative PL intensity of AIEgens should increase in high‐viscous environment due to the limited molecular motions . We further carried out a viscosity study to confirm the ESDBR effect in the synthesized AIEgens (Figures c and d).…”
Section: Resultsmentioning
confidence: 99%
“…This is resulting from the efficiently restricted ESDBR effect by the intermolecular H‐bonding interaction upon fluoro‐substitution. Furthermore, according to Förster–Hoffmann power‐law relationship, the relative PL intensity of AIEgens should increase in high‐viscous environment due to the limited molecular motions . We further carried out a viscosity study to confirm the ESDBR effect in the synthesized AIEgens (Figures c and d).…”
Section: Resultsmentioning
confidence: 99%
“…There is no doubt that high viscosity would restrict the intramolecular rotations and directly decrease the rapid non‐radiative decay. Thus, a turn on emission could be seen in more viscous media which might be applied in the measurement of viscosity or in the fast detection of the leaking oil [16,17] …”
Section: Resultsmentioning
confidence: 99%
“…Thus, a turn on emission could be seen in more viscous media which might be applied in the measurement of viscosity or in the fast detection of the leaking oil. [16,17] Thus, we tested the fluorescent response of these three compounds to the viscosity by simply increasing the fraction of glycerol in methanol. When adding glycerol into their dilute MeOH solutions, emissive spectra of compound 1 were slightly changed as the glycerol fraction changed from 0 to 90% ( Figure S17).…”
Section: Restriction Intramolecular Rotation and Viscosity Measurementmentioning
confidence: 99%
“…Thus, it is possible that a less bulky group (than phenyl) on meso -position of BODIPY with substituents on the 1,7-positions may allow the rotation in non-viscous media and thus might provide an alternative strategy for designing BODIPY based efficient micro-viscosity probes. Indeed, Yu et al recently reported a meso -2-ketopyrrolyl-derived BODIPY 10 as a new FMR containing substituents on the 1,7-positions (Figure 1J; Yu et al, 2019). The fluorescence lifetime (log τ) of BODIPY 10 has a linear relationship with viscosity (log η).…”
Section: Introductionmentioning
confidence: 99%